2019
DOI: 10.1016/j.jddst.2019.101192
|View full text |Cite
|
Sign up to set email alerts
|

Influence of mesoporous silica on powder flow and electrostatic properties on short and long term

Abstract: We study the effect of three types of mesoporous silica (MPS) particles on the flow of three common excipients: microcrystalline cellulose, lactose and maize starch. While MPS are commonly considered as excipient and also as drug delivery carrier, the effects of MPS as flow aid additive and as powder stabilizer are investigated. MPS particles, called additive in the present study, are found to decrease powder cohesiveness, in particular for powders having higher water content and higher initial cohesiveness. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 37 publications
1
21
0
Order By: Relevance
“…This shear thinning behavior could be explained by a powder aeration at higher speeds. A similar decrease in cohesive index and shear thinning at increasing speeds was observed for lactose blended with 2% Mesoporous silica before testing (Lumay et al, 2019).…”
Section: Compact Feeder Equipmentsupporting
confidence: 72%
See 1 more Smart Citation
“…This shear thinning behavior could be explained by a powder aeration at higher speeds. A similar decrease in cohesive index and shear thinning at increasing speeds was observed for lactose blended with 2% Mesoporous silica before testing (Lumay et al, 2019).…”
Section: Compact Feeder Equipmentsupporting
confidence: 72%
“…The DC grades have been co-processed using a small amount of silicon dioxide which may provide both a mitigation against triboelectric charging as well as a flow aid. Similarly, mesoporous silica was studied in combination with lactose, starch and microcrystalline cellulose and was shown to decrease the charging of those materials (Lumay et al, 2019). This is surprising since colloidal silicon dioxide on its own was shown to have the most negative chargeability of the materials studied and had the most electrostatic accumulation (Ramirez-Dorronsoro et al, 2006).…”
Section: Triboelectric Charging Of Hpmcmentioning
confidence: 99%
“…The powder charge can vary by varying the material that they contact during process. In addition, it has been reported that the surface formulation of powders or addition of additive can change the sign of particle charge or modify the quantity of charge [12]. In the same study on lactose powder they noticed that by adding syloid 244FP to the lactose powder it gets negative final charge, while by addition syloid XDP 3050 to lactose powder it gets positive charge also by increasing the quantity of both additives the charge of both powders have started to decrease.…”
Section: Chargementioning
confidence: 96%
“…In general, a powder can obtain negative or positive charge after flow, based on their tendency to obtain or loss electron [6]. As an instance, in a study on lactose powder it has been observed that at low relative humidity lactose powder charges positively while at higher relative humidity it charged negatively in fact the relative humidity here played role in tendency of powder to be charged with different sign [12]. The powder charge can vary by varying the material that they contact during process.…”
Section: Chargementioning
confidence: 99%
“…In case of silicate application as a glidant, the usual concentration in a formulation is up to 1%. Currently, available literature concerning this topic is mainly focused on finding new glidants, optimal process conditions leading to the highest glidant effectiveness, or further understanding of glidant mechanism of action [ 48 , 49 , 50 , 51 , 52 , 53 , 54 ].…”
Section: Introductionmentioning
confidence: 99%